Forecasting the Energy Capacity of Petrochemical Productions Under Conditions of Technological Transformations - Gallyamova, Dinara Kh.; Shinkevich, Marina V. (International Journal of Energy Economics and Policy, 2022)
The purpose of the study is to identify patterns of energy-saving development of the petrochemical industry in the context of the introduction of innovations and to predict the energy intensity of the industry based on economic and mathematical modeling. As part of achieving the goal, an analysis of the series of dynamics was carried out and prognostic methods based on variant correlation analysis and regression modeling were applied. At the first stage of the study, the dynamics of energy consumption and costs of innovative activities in the development of petrochemical industries in Russia was assessed; at the second stage, a predictive model of changes in the energy intensity of petrochemical industries was built. As a result of the study, the regularities of the development of petrochemical industries in Russia were revealed (stable reduction in energy consumption, unstable dynamics of unit costs for innovative activities of petrochemical industries); the nature of the influence of technological modernization of production on the level of energy intensity is determined, which is manifested in the difference in sectoral accents of innovative development; regression equations are proposed, reflecting the dependence of the energy intensity of petrochemical industries on the volume of sales of industry products; calculated the predicted values of energy intensity, allowing to develop a set of management measures to support the energy efficient development of industry in Russia. The formulated conclusions and results can serve as a basis for improving the strategic directions of development of the petrochemical industry in Russia, taking into account the prioritization of the implementation of energy-saving innovative solutions.